Hubungan Literasi Keuangan dengan Financial Behavior Pada Mahasiswa Ekonomi dan Bisnis - Afysca Maharani Dyan Fystari; Ana Kadarningsih (Akuntansi, 2023)
Today, financial problems have become commonplace in everyday life. Many students have difficulty managing their finances. This is caused by a lack of financial literacy among students, the lifestyle of each individual, and the financial attitude of each student. The population of this research is all students from the Faculty of Economics and Business. The sample criteria are FEB students class 2020 – 2021. The sampling method that meets the criteria is purposive sampling which is carried out by distributing questionnaires via Google Form. The sample collected from distributing questionnaires was 275 data and only 272 data met the criteria and could be processed. Research analysis uses SEM PLS with Smart PLS software Version 4.0